Performance analysis of radio propagation models in VANET application - Shuhaimi, Nurain Izzati; Ashmadi, Nur Liyana; Abdullah, Ezmin; Mohamad, Roslina; Mohamad, Sarah Yasmin (IEEE, 2021)
Vehicular Ad-hoc Network (VANET) is developed for the communication between vehicle-to-vehicle and vehicle-to-roadside in purpose for safety, navigation and other roadside services. The radio propagation model (RPM) was used in VANET for the implementation of VANET in order to estimate the path loss in multiple operating environments such as modern road infrastructure. This research is concerned with the study about the performance of different RPM on VANET between Free Space propagation, Two Ray Ground propagation and Nakagami propagation. The purpose of this research work is to observe the packet loss, throughput and average end-to-end delay between vehicles by implementing different type of RPMs, which then has been compared to determine which RPM has a better performance. To obtain the performance analysis of RPM in VANET, several software such as Java OpenStreetMap (JOSM), Simulator of Urban Mobility (SUMO), Mobility Model Generator for VANET (MOVE) and Network Simulator Version 2 (NS2) has been used with Linux Ubuntu version 20.04 as the operating system. The data were collected at Jalan Besar Selayang Baru, 68100 Batu Caves, Selangor. With the target location of 2 km x 2 km size, detail analyzation of data from all three different propagation models were performed. Hence, the best performance of RPM in VANET has been identified.